Composición y abundancia de búhos en el Parque Nacional Sierra de San Pedro Mártir, Baja California, México - Rodríguez-Hernández, Irak; De León-Girón, Gonzálo; Ganoa-Melo, Tonatiuh; Enríquez, Paula L.; Ruiz-Campos, Gorgonio (Instituto de Ecología, A.C., 2022)
The composition and abundance of owls were seasonally determined at four sites of the Sierra de San Pedro Mártir National Park, Baja California (PNSSPM), Mexico, by means of the call-listening technique from October 2017 to August 2018. A total of 60 records of seven species was obtained (Northern Saw-whet Owl Aegolius acadicus, Long-eared Owl Asio otus, Great Horned Owl Bubo virginianus, Northern Pygmy-Owl Glaucidium californicum, Western Screech-Owl Megascops kennicottii, Flammulated Owl Psiloscops flammeolus, and Spotted Owl Strix occidentalis). The species with the highest average frequency of records (individuals/h) was B. virginianus (4.04), while other species recorded frequencies from 0.2 (S. occidentalis) to 1.1 (M. kennicottii and A. otus). Two species were permanent residents (B. virginianus and M. kennicottii), one summer visitor (A. acadicus), one winter visitor (A. otus), and three occasional visitors (P. flammeolus, G. californicum and S. occidentalis). The species richness of owls in the PNSSPM increased in winter due to the presence of migratory species.